Mechanistic insights into low-dose nZVI-enhanced process stability under variable industrial loads in field-scale anaerobic treatment: Interfacial evolution and strain-resolved adaptation - Zhihong Gao; Lijing Xue; Yujia Ma; Chen Chen; Hong Ling; Lin Wang; Weiming Zhang; Jieshu Qian; Zhichao Yang; Ming Hua; Bingcai Pan (Water Research, 2026)

Iron availability as a time-evolving descriptor linking syntrophic metabolic responses and process performance in nano-iron-amended anaerobic systems - Yujia Ma; Lijing Xue; Zhihong Gao; Chen Chen; Lin Wang; Ming Hua; Zhichao Yang; Chao Shan; Jieshu Qian; Hongchao Li; Weiming Zhang (Bioresource Technology, 2026)

Polymer-dependent accumulation of PFASs on microplastics in Xiamen Bay: field evidence and laboratory partitioning - Haitao Lin; Weiming Kuang; Jincheng Sun; Rupeng Du; Weiming Wu; Zhuoyun Chen; Liang Wang; Zhong Pan (Water Research, 2026)

Artificial Intelligence and Protein Design: A retrospective study on 20-year emerging trends and core research areas from bibliometric perspectives - Wenjuan Zhao; Xiuwu Pan; Wei Yang; Zichang Liu; Xiyi Wei; Anqi Lin; Bufu Tang; Lin Zhang; Mingjia Xiao; Qing Zeng; Quan Cheng; Weiming Mou; et al. (Probiotics and Antimicrobial Proteins, 2026)

Integrated hydrothermal and photocatalytic strategy for PET microplastic conversion and waste valorization - Liangbin Lin; Huizhen Lin; Jiawei Huang; Luteng Luo; Qinyun Qiu; Wenxiu Wu; Zhipeng Zhang; Hao Xue; Bingqi Jiang; Qingrong Qian; Qinghua Chen; Changlin Cao; et al. (Chemical Engineering Journal, 2026)

A layered classification framework of near-infrared waste plastic identification through interpretable machine learning - Keyu Zhu; Junrong Chen; Ruizhe Tu; Changlin Cao; Weiming Zhou; Songwei Yang; Qingrong Qian; Qinghua Chen; Kunsen Lin (Journal of Environmental Chemical Engineering, 2026)

Deciphering the indigenous microbiome enables rational design of functional starter cultures to enhance platycodins in fermented Platycodon grandiflorus - Yulian Zhao; Haisu Shi; Junrui Wu; Lin Shi; Weiming Wang; Lin Yao; Meijun Song; Tenghe Ma; Lin Ye; Rina Wu (Food Bioscience, 2026)

Structural determinants of gelation kinetics in rambutan seed starches: Implications for enhanced precision in 3D food printing - Rui He; Yuxuan Li; Xiaoyu Lin; Bo Xu; Xiang Huo; Weiming Zhang; Tao Yang; Geng Zhong; Fengwei Xie; Ying Chen (Carbohydrate Polymers, 2026)

Detrital zircon UPb and fission track double dating constraints on the exhumation history of Longmen Mountains: New insights into proto-Tibetan Plateau evolution - Xu Lin; Siyu Han; Lin Wu; Marc Jolivet; Dongliang Liu; Zhonghai Wu; Weiming Liu; Jing Liu-Zeng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Impacts of hydrological conditions and sediment properties on community structure and activity of phosphorus-transforming microbes in a cascade reservoir system - Fangjie Zhang; Xiong Pan; Weijie Wu; Weiming Tan; Jiayu Guo; Longfei Wang; Li Lin (Journal of Water Process Engineering, 2026)

Fused deposition modelling 3D printing incorporates BiOCl morphology regulation as a strategy for developing bespoke photocatalytic reactor - Changlin Cao; Xinshu Xia; Liangbin Lin; Songwei Yang; Yan Li; Weiming Zhou; Lihong Xu; Qinghua Chen; Qingrong Qian (Journal of Environmental Management, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Mesozoic and Cenozoic paleogeography reconstruction of the western Jianghan Basin (Central China): Revealed by apatite fission track dating - Xu Lin; Xia Zhong; Weiming Liu (Journal of Mountain Science, 2026)

Shadow under the lamp: Evidence-based assessments reveal local extirpation risk of large Indian civets (Viverra zibetha) concealed by intensive activity in human-dominated landscapes - Weiming Lin; Yue Weng; Hongmin Wang; Minhui Li; Qi Wang; Jia A; Qing Zhao; Fang Wang (Biological Conservation, 2026)

Unraveling the exhumation history of the source terrains of the western Jianghan Basin (Central China) through detrital zircon fission track dating - Siyu Han; Xu Lin; Weiming Liu; Haijin Liu (Journal of Mountain Science, 2026)

Low-altitude remote sensing and deep learning-based canopy detection method for the navigation of orchard unmanned ground vehicles - Yongda Lin; Xiaofei Song; Weiming Xiao; Dongdong Kuang; Shiyu Xia; Honggen Chang; Supakorn Wongsuk; Xiongkui He; Yajia Liu (Computers and Electronics in Agriculture, 2025)

Neogene integration of the upper Yellow River drainage system: Insights from detrital zircon U Pb geochronology in the Laolongwan Basin, Northeastern Tibetan Plateau - Xu Lin; Haijin Liu; Weiming Liu; Lin Wu; Siyi Li; Ziwen Zhou; Xinling Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A novel approach for wave-turbulence decomposition - Jianliang Lin; Chunyan Zhu; Jianwei Sun; Weiming Xie; Bram van Prooijen; Leicheng Guo; Qing He; Qingshu Yang; Zheng Bing Wang (Coastal Engineering, 2025)

Aerosol sampling-based infection risk model for spatiotemporal resolution informed evaluation of on-site transmission risk - Han Gao; Weihao Li; Mengqing Cheng; Danting Luo; Manman Lv; Haotian Yu; Yemin Han; Weiming Lin; Yan Huang; Dianhuai Meng; Tian Weng; Qiang Zhang; et al. (Journal of Hazardous Materials, 2025)

Dual-PROTACs based on natural product derivative potassium dehydrographolide succinate: design, synthesis, and antitumor activity of a novel EGFR degrader - Ruling Shi; Peixi Zhang; Ming Chen; Weiming Lu; Meng Xu; Huagong Zeng; Jie He; Yan Wang; Yirong Lin; Jieqing Liu (Medicinal Chemistry Research, 2025)

Multi-asymmetry on residual sediment transport in the branching channels of the Yangtze Estuary - Simin Zhou; Chunyan Zhu; Jianliang Lin; Weiming Xie; Naiyu Zhang; Leicheng Guo; Qing He (Journal of Hydrology, 2025)

Geological significance of late Cretaceous exhumation in Jiuhua Mountain: Insights from zircon (U-Th)/He dating - Yuxuan Pang; Xu Lin; Weiming Liu; Jing Liu-Zeng; Lin Wu; Haijin Liu (Journal of Mountain Science, 2025)

Provenance of the detrital deposits in the Daju Basin of the Jinsha River, China - Lingling Li; Weiming Liu; Xu Lin; Anna Yang; Xuemei Li; Zewen Yang; Huimin Zhao (Journal of Geographical Sciences, 2025)

Optimizing application strategies of prohexadione-calcium·uniconazole composite regulator to improve lodging resistance and grain yield in rice cultivation in East China - Dengke Ma; Yimin Ding; Yifan Liu; Lin Du; You Mo; Ali Dai; Junyan Xu; Dalu Gu; Liusheng Duan; Weiming Tan (Field Crops Research, 2025)

Electrochemistry sensing of ascorbic acid based on conductive metal-organic framework (Cu3(benzenehexathiol)) nanosheets modified electrode - Runhao Yuan; Xiaolong Zhong; Weiming Sun; Jian Wang; Chuanhui Huang; Zhenyu Lin; Jianping Zheng (Analytica Chimica Acta, 2025)

Monthly variations of the spring greenness response across boreal Eurasia to the preceding wintertime northern annular mode during 1982–2022 - Jing Li; Weiming Zeng; Ruichen Lin; Zhiqing Xu; Xilin Xie; Feng Su; Rui Zhao; Anmin Duan (Climate Dynamics, 2025)

Deciphering the promotion and inhibition of bicarbonate fertilization on microalgal activity and nutrient uptake from wastewater - Shuohui Shi; Ying Zhang; Shuxuan Lin; Meiman Zhang; Weiming Zou; Jian Zhou; Yingmu Wang (Journal of Environmental Management, 2025)

LINC01224 promotes the Warburg effect in gastric cancer by activating the miR-486-5p/PI3K axis - Yuling Bin; Minji Liu; Rong He; Pingfei Tang; Weiming Qu; Dajun Wu; Lin Tan; Qian Wang; Peng Jiang; Hongsai Hu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Biodegradation of commercial polyester polyurethane by a soil-borne bacterium Bacillus velezensis MB01B: Efficiency, degradation pathway, and in-situ remediation in landfill soil - Jie Zeng; Junruo Yao; Weiming Zhang; Miaomiao Zhang; Tan Wang; Xun Yu; Yongxuan Liu; Xiaowen Sun; Lin Li (Environmental Pollution, 2024)

Conductive hydrogel with responsive release of Herbal-Derived carbon dots for neurovascular reconstruction in diabetic critical limb ischemia - Zhibin Zhou; Mengzhen Zhao; Huaqiang Fang; Ziyue Lin; Xinrui Zheng; Yi Zhuo; Zimeng Li; Weiming Zhou; Xiaolei Wang (Chemical Engineering Journal, 2024)

Fractionation, spatial distribution, ecological and health risk assessment of cobalt and nickel in surface sediment of a bay along the southeast coast of China - Yang Liu; Weiming Kuang; Xiuwu Sun; Weili Wang; Cai Lin; Hui Lin (Marine Pollution Bulletin, 2024)

The role of tissue-derived extracellular vesicles in tumor microenvironment - Jin Lin; Wan Lu; Bo Huang; Weiming Yang; Xiaozhong Wang (Tissue and Cell, 2024)

Soat2 inhibitor avasimibe alleviates acute pancreatitis by suppressing acinar cell ferroptosis - Weiwei Luo; Lin Chen; Hui Sun; Siqin Zhang; Xiaowu Dong; Jiajia Pan; Weiming Xiao; Guotao Lu; Yaodong Wang; Hongwei Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Sources of suspended sediments in salt marsh creeks: Field measurements in China and the Netherlands - Jianwei Sun; Bram van Prooijen; Xianye Wang; Jill Hanssen; Weiming Xie; Jianliang Lin; Yuan Xu; Qing He; Zhengbing Wang (Geomorphology, 2024)

Exploring the roles of excess amino acids, creatine, creatinine, and glucose in the formation of heterocyclic aromatic amines by UPLC-MS/MS - Haolin Zhang; Xiaomei Lv; Weiming Su; Bing-Huei Chen; Yu-Wen Lai; Ruiwei Xie; Qiuyi Lin; Lei Chen; Hui Cao (Food Chemistry, 2024)

Geoarchaeological evidence of an ancient landslide dam (13–4.7 ka) and consequent outburst flood on the Minjiang River near Wenchuan, China - Niannian Fan; Xingguo Yang; Michael J. Storozum; Xuefeng Cheng; Lan Li; Weiming Liu; Zhipeng Lin; Xingnian Liu (CATENA, 2024)

Sophisticated construction of single-atom cobalt catalyst based on microbial hyphae for high-performance hydrogenation - Junhua Kuang; Minghao Gong; Gaofeng Chen; Li Peng; Chen Zou; Zhiqing Peng; Weiming Chen; Yin Li; Yuting Zhang; Tianwei Xue; Chuang Li; Yangyang Dong; et al. (Chemical Engineering Journal, 2024)

A short-term of starvation improved the antioxidant activity and quality of African catfish (Clarias gariepinus) - Fanbin Zhan; Qingqing Li; Huiwen Feng; Ruikang Lin; Weiming Liang; Li Lin; Zhendong Qin (Fish Physiology and Biochemistry, 2024)

Crack Coalescence Mechanism and Crack Type Determination Model Based on the Analysis of Specimen Apparent Strain Field Data - Tao Dong; Ju Wang; Weiming Gong; Fei Wang; Hongguang Lin; Wengbo Zhu (Rock Mechanics and Rock Engineering, 2024)

Mechanism of rapid accretion-erosion transition in a complex hydrodynamic environment based on refined in-situ data - Jie Jiang; Weiming Xie; Naiyu Zhang; Yuan Xu; Chunyan Zhu; Jianliang Lin; Leicheng Guo; Jian Shen; Qing He (Frontiers in Marine Science, 2024)
Morphological changes in estuaries are typically discussed on decadal time scales, with reported changes often exceed several decimeters. In our study, we utilized refined in-situ data to investigate bed-level changes and rapid accretion-erosion transitions during tidal cycles off the Changjiang Estuary. A field study employing a high-resolution bottom tripod system was conducted, measuring various parameters such as water level, waves, velocity profiles, near-bottom suspended sediment concentration (SSC), and bed level changes over ten tidal cycles. Our findings reveal significant and intense bed level changes occurring at the scale of tidal cycles. The data suggests that downward sediment transport plays a dominant role in the overall accretion tendency throughout the study period. Additionally, our research introduces a dynamic critical bed shear stress that increases during tidal cycles, deviating from fixed values. We also present a new quadrant analysis method to elucidate the primary processes controlling near-bed sediment transport. The results highlight the importance of horizontal advective sediment transport in frequent accretion-erosion transitions at tidal-cycle timescales. This implies a frequent exchange of sediment between adjacent shoals and channels in the seaward region of the North Channel in the Changjiang Estuary, which holds significance for future navigation and construction management.

Different effects between cold front and tropical cyclone on short-term morphodynamics in the Changjiang Delta - Xuefeng Wu; Qing He; Jian Shen; Zhong Peng; Leicheng Guo; Weiming Xie; Jianliang Lin (Journal of Marine Systems, 2024)

Impact of urban land development on carbon emission performance based on a multidimensional framework - Xinhui Feng; Xinle Lin; Yan Li; Jiayu Yang; Er Yu; Congying He; Kaige Lei; Weiming Gao (Environmental Impact Assessment Review, 2024)

Design, Synthesis and Biological Evaluation of Novel 1H-1,2,4-Triazole Derivatives as Strigolactone Biosynthesis Inhibitors - Lin Du; Jijun Yan; Chunxin Yu; Chunying Wang; Weiming Tan; Liusheng Duan (Journal of Plant Growth Regulation, 2024)

Structural design of Janus lamellar membrane based on bismuth oxychloride for comprehensive solar energy utilization - Weiming Zhou; Hongqiang Huang; Chong Wang; Liwei Wang; Xiangfeng Lin; Yusuke Asakura; Yusuke Yamauchi; Sameh M. Osman; Zhanhui Yuan (Chemical Engineering Journal, 2024)

A Real-World Study of Patient and Physician Satisfaction With AbobotulinumtoxinA Treatment of Glabellar Lines in Chinese Patients - Cecilia Persson; Jianmei Huang; Zhongrong Jiang; Li Ma; Jingjing Zhao; Zhiqiang Xue; Shuxian Zhang; Yuan Chen; Weiming Song; Lin Tao; Qingyang Liu; Inna Prygova (Toxicon, 2024)

Redefining virtual water allocation in China based on economic welfare gains from environmental externalities - Yiyi Cao; Yunlei She; Qianzi Wang; Jin Lin; Weiming Chen; Shen Qu; Zhouyi Liu (Journal of Cleaner Production, 2024)

Sedimentary provenance constraints on the Cretaceous to Cenozoic palaeogeography of the western margin of the Jianghan Basin, South China - Xu Lin; Jing Liu-Zeng; Marc Jolivet; Weiming Liu; Feng Cheng; Haijin Liu; Lingling Li; Jixin Chen; Chengwei Hu; Xiaokang Chen (Gondwana Research, 2024)

Solidification/stabilisation behaviours of Zn2+ in magnesium potassium phosphate cement: Experiments and density functional theory study - Renjie Mi; Zhibin Zhang; Weiming Ji; Shichang Liu; M.F. Kai; Kui lin; Yongshan Tan (Environmental Research, 2023)

The interference between effects of PFAS exposure on thyroid hormone disorders and cholesterol levels: an NHANES analysis - Liang Zheng; Zhecun Wang; Rui Yang; Wanna Chen; Jing Zhang; Ruixia Li; Weiming Lv; Bo Lin; Jiajun Luo (Environmental Science and Pollution Research, 2023)

Design, Synthesis and Herbicidal Evaluation of Novel Urea Derivatives with Inhibition Activity to Root Growth - Lin Du; Zhikun Yang; Huiqi Zhang; Keke Yu; Xing Wang; Weiming Tan; Liusheng Duan (Journal of Plant Growth Regulation, 2023)

Characterization, source identification, risk assessment of potentially toxic elements (PTEs) in the surface water and sediment of the Beibu Gulf, China - Yang Liu; Ronggen Jiang; Weiming Kuang; Cai Lin; Xiuwu Sun; Jinmin Chen; Zhong Pan (Marine Pollution Bulletin, 2023)

Phytochemical and chemotaxonomic investigations on the aerial parts of Cynanchum auriculatum Royle ex Wight - Yanling Xu; Chenyang Wu; Lu Wang; Shengbo Wu; Yueru Chen; Xiaoxue Ding; Lin Wang; Yi Yu; Weiming Du; Yuqing Zhang; Rachel Y.H. Yang; Jian Hong; et al. (Biochemical Systematics and Ecology, 2023)

Research on a DC–DC Converter and Its Advanced Control Strategy Applied to the Integrated Energy System of Marine Breeding Platforms - Hongxing Chen; Weiming Lin; Wei He (Journal of Marine Science and Engineering, 2023)
The deep-sea aquaculture industry will become one of the important pillars of the future marine economy. However, the application of clean energy in the new scenario needs to be strengthened for platform operation. For this kind of renewable-energy distributed-generation system, an energy storage system is essential. A bidirectional DC–DC converter is essential for distributed power generation systems. It connects a variety of renewable energy sources with energy storage cells. A high-gain bidirectional Cuk circuit with zero ripple is proposed in the paper. It is characterized by a simple structure, zero ripple, low voltage stress of semiconductor power devices, and high voltage gain. A passivity-based control with linear active disturbance rejection is proposed to solve the problems of the large steady-state error. The zero steady-state error, strong robustness, and whole-range stability have been obtained for the proposed control strategy. Finally, a simulation was carried out. A 100 W, 48 V/400 V prototype was built to verify the validity of the theoretical analysis for the proposed circuit. The improved passivity-based control strategy was verified to solve the contradiction between rapidity and overshoot. It can be realized to improve the dynamic performance of the proposed converter and achieve robust control.

Full-scale field test study of bearing characteristics of post-grouting pile for offshore wind turbines - Weiming Gong; Zhitong Zhang; Yifeng Lin; Guoliang Dai; Hao Huang (Ocean Engineering, 2023)

HBRWRLDA: predicting potential lncRNA–disease associations based on hypergraph bi-random walk with restart - Guobo Xie; Yinting Zhu; Zhiyi Lin; Yuping Sun; Guosheng Gu; Jianming Li; Weiming Wang (Molecular Genetics and Genomics, 2022)

Predicting circRNA-Disease Associations Based on Deep Matrix Factorization with Multi-source Fusion - Guobo Xie; Hui Chen; Yuping Sun; Guosheng Gu; Zhiyi Lin; Weiming Wang; Jianming Li (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Preliminary study on relationships among nutritional risk, serum prealbumin, and peripheral blood T cell subsets in patients with severe COVID-19 - Yanli Li; Yanbo Sun; Jing He; Peng Zhao; Pengju Luo; Jinsong Bai; Weiming Li; Shumin Li; Yueying Lin; Yunyun Cen (Infectious Diseases, 2021)

A 3-D finite volume model for sediment transport in coastal waters - Weiming Wu; Qianru Lin (Ocean Dynamics, 2019)

Comparative Analysis of Regulatory Role of Notch Signaling Pathway in 8 Types Liver Cell During Liver Regeneration - Xianguang Yang; Chuncui He; Lin Zhu; Weiming Zhao; Shuaihong Li; Cong Xia; Cunshuan Xu (Biochemical Genetics, 2019)

The complete mitochondrial genome of the grey bamboo shark (Chiloscyllium griseum) (Orectolobiformes: Hemiscylliidae): genomic characterization and phylogenetic application - Xiao Chen; Weiming Ai; Le Ye; Xuehui Wang; Chongwen Lin; Shengyun Yang (Acta Oceanologica Sinica, 2013)

The genetic association of adakites and Cu–Au ore deposits': a reply - Weidong Sun; Mingxing Ling; Xing Ding; Sun-Lin Chung; Xiao-Yong Yang; Weiming Fan (International Geology Review, 2012)

The genetic association of adakites and Cu–Au ore deposits - Weidong Sun; Hong Zhang; Ming-Xing Ling; Xing Ding; Sun-Lin Chung; Jibin Zhou; Xiao-Yong Yang; Weiming Fan (International Geology Review, 2011)

Higher rates of nitrogen fertilization decrease soil enzyme activities, microbial functional diversity and nitrification capacity in a Chinese polytunnel greenhouse vegetable land - Weishou Shen; Xiangui Lin; Weiming Shi; Ju Min; Nan Gao; Huayong Zhang; Rui Yin; Xinhua He (Plant and Soil, 2010)

Liquefaction macrophenomena in the great Wenchuan earthquake - Longwei Chen; Xiaoming Yuan; Zhenzhong Cao; Longqing Hou; Rui Sun; Lin Dong; Weiming Wang; Fanchao Meng; Hongjuan Chen (Earthquake Engineering and Engineering Vibration, 2009)

Land use intensification affects soil microbial populations, functional diversity and related suppressiveness of cucumber Fusarium wilt in China’s Yangtze River Delta - Weishou Shen; Xiangui Lin; Nan Gao; Huayong Zhang; Rui Yin; Weiming Shi; Zengqiang Duan (Plant and Soil, 2008)

Overexpression of a Panax ginseng tonoplast aquaporin alters salt tolerance, drought tolerance and cold acclimation ability in transgenic Arabidopsis plants - Yanhui Peng; Wuling Lin; Weiming Cai; Rajeev Arora (Planta, 2007)

Mercury pollution from small gold mines in China - Yuhuan Lin; Mingxin Guo; Weiming Gan (Water, Air, & Soil Pollution, 1997)

Mercury Pollution from Small Gold Mines in China - Yuhuan Lin; Mingxin Guo; Weiming Gan (Water, Air, & Soil Pollution, 1997)